2019
DOI: 10.1021/acsaelm.9b00719
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of CVD Graphene Directly on Dielectric Surface toward Application

Abstract: A technique for the in situ growth of patterned graphene by CVD has been achieved directly on insulating substrates at 800 °C. The graphene growth is catalyzed by a Ni−Cu alloy sacrificial layer, which integrates many advantages such as being lithography-free, and almost wrinkle-free, with a high repeatability and rapid growth. The etching method of the metal sacrificial layer is the core of this technique, and the mechanism is analyzed. Graphene has been found to play an important role in accelerating etching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
0
19
1
2
Order By: Relevance
“…It shows that with the increase of Ni percentage, the graphene grown at 600 °C becomes thicker and appears with uneven layer distribution. Even though such a phenomenon was observed in our previous work [15] on the graphene growth at a higher temperature, i.e., 800 °C, it seemed contrary to our expectations, considering the limited carbon solid solubility at low temperatures. We found that this phenomenon could no longer be explained by the known mechanism of carbon atom segregation.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…It shows that with the increase of Ni percentage, the graphene grown at 600 °C becomes thicker and appears with uneven layer distribution. Even though such a phenomenon was observed in our previous work [15] on the graphene growth at a higher temperature, i.e., 800 °C, it seemed contrary to our expectations, considering the limited carbon solid solubility at low temperatures. We found that this phenomenon could no longer be explained by the known mechanism of carbon atom segregation.…”
Section: Resultscontrasting
confidence: 99%
“…Ni is known to be more catalytic than Cu in graphene growth [14]. Previously, we have studied the growth of graphene at 800 °C and found that with the increase of Ni composition in Ni–Cu alloys, the quality of graphene increased gradually [15]. However, the carbon solid solubility of Ni–Cu alloy also increases with the increase of Ni composition [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Dong et al focuses on the in situ growth of patterned graphene structures via a vertical cold wall CVD reactor using a SiO 2 /Si substrate and Ni-Cu alloy sacrificial layer as a metal catalyst at 800 • C. The Ni-Cu alloy is particularly suitable to be used as a growth substrate for graphene at low temperatures due to its catalytic nature, low carbon solubility (about 4.3 times lower than that of pure Ni), and more uniform grain size compared with Cu and Ni. Due to these advantages of the Ni-Cu alloy, the graphene film obtained by the proposed method exhibited excellent uniformity and a high monolayer ratio [89].…”
Section: Cold-wall Cvdmentioning
confidence: 99%